1986
DOI: 10.3181/00379727-183-42385
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Atrial Appendectomy on Circulating Atrial Natriuretic Factor during Volume Expansion in the Rat

Abstract: This study examined the changes in the circulating level of endogenous atrial natriuretic factor during diuresis and natriuresis produced by acute volume expansion in anesthetized rats with either bilateral atrial appendectomy ( n = 9) or sham operation ( n = 9). Following control measurements in the sham-operated rats, 1 % body weight volume expansion with isotonic saline produced an increment in urinary sodium excretion of over 4 peqlmin ( P < 0.05) while urine volume increased by more than 20 pl/min ( P < 0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

1987
1987
1997
1997

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…Atrial appendectomy in the rat has been shown to attenuate both the rise in ANF (4) and the natriuresis (3,4) in response to acute volume expansion. This response can also be attenuated by prior administration of monoclonal antibodies directed against ANF (5).…”
Section: Discussionmentioning
confidence: 99%
“…Atrial appendectomy in the rat has been shown to attenuate both the rise in ANF (4) and the natriuresis (3,4) in response to acute volume expansion. This response can also be attenuated by prior administration of monoclonal antibodies directed against ANF (5).…”
Section: Discussionmentioning
confidence: 99%
“…These facts may explain the inconsistency between appendage dimensional changes in the present study and the flow pattern described by Suetsugu et al12) Some previous studies have shown that left atrial appendectomy caused few hemodynamic changes. 13,14) The left appendage may not be important in hearts with an intact left ventricle. In this study, however, the appendage clearly acted as a booster pump showing greater fractional shortening than the atrial body , and moreover, the appendage had a Frank Starling mechanism during volume loading similar to that of the atrial body .…”
Section: Discussionmentioning
confidence: 99%
“…Removal of the atrial appendages, which are major storage sites for proANF, blunted the volume-induced increase in plasma ANP and reduced the ability of anesthetized 9 ' 10 and conscious" rats to excrete an acute intravenous volume load. This suggested that less ANF was available for release in the rats that had undergone atrial appendectomy, and that an attenuated increment in plasma ANF level accounted for the blunted natriuretic and diuretic responses.…”
Section: Ratsmentioning
confidence: 99%